Georgia Rising : Sustaining Rapid Economic Growth - World Bank (Washington, DC, 2013)
Economic growth in Georgia was strong at 6.1 percent per year during 2004-12 as structural reforms and a favorable global economy led to large foreign direct investment (FDI) inflows and expansion in the services sectors. However, the current account deficit has remained large and economic expansion has been driven primarily by the nontradable sectors, thus raising concerns about the sustainability of growth. This country economic memorandum (CEM) report shows that sustaining strong growth in Georgia going forward will require new policies that help support both high investment financed increasingly from domestic sources as well as sustained rapid productivity growth in the export and tradable sectors. The report presents an array of policy options to raise national saving, boost firm productivity, better deploy labor resources, and enhance export competitiveness. Raising national saving will require a shift in the fiscal framework to control growth of current expenditures and bolstering private saving through macro-prudential regulations and a package of measures to support saving for retirement. Stimulating firm productivity will require addressing a range of constraints, including streamlining the complexity of closing a business, reducing high borrowing costs, and improving the electricity pricing mechanism. Boosting job creation and more productively deploying labor resources will require upgrading overall education quality, strengthening vocational education systems, and developing job matching services to alleviate skills mismatches and reduce search costs. Enhancing competitiveness of exports will require addressing any overvaluation of the exchange rate, pursuing trade-related reforms to enhance access to European Union and international markets, and upgrading logistics and internal infrastructure.